Are thyrotropin‐releasing hormone (TRH) and analog taltirelin viable reversal agents of opioid‐induced respiratory depression?. Issue 3 (27th May 2022) - Algera, Marieke Hyke; Cotten, Joseph F.; van Velzen, Monique; Niesters, Marieke; Boon, Martijn; Shoham, Daniel S.; Dandrea, Kaye E.; van der Schrier, Rutger; Dahan, Albert
Abstract: Opioid‐induced respiratory depression (OIRD) is a potentially life‐threatening complication of opioid consumption. Apart from naloxone, an opioid antagonist that has various disadvantages, a possible reversal strategy is treatment of OIRD with the hypothalamic hormone and neuromodulator thyrotropin‐releasing hormone (TRH). In this review, we performed a search in electronic databases and retrieved 52 papers on the effect of TRH and TRH‐analogs on respiration and their efficacy in the reversal of OIRD in awake and anesthetized mammals, including humans. Animal studies show that TRH and its analog taltirelin stimulate breathing via an effect at the preBötzinger complex, an important respiratory rhythm generator within the brainstem respiratory network. An additional respiratory excitatory effect may be related to TRH's analeptic effect. In awake and anesthetized rodents, TRH and taltirelin improved morphine‐ and sufentanil‐induced respiratory depression, by causing rapid shallow breathing. This pattern of breathing increases the work of breathing, dead space ventilation, atelectasis, and hypoxia. In awake and anesthetized humans, a continuous infusion of intravenous TRH with doses up to 8 mg, did not reverse sufentanil‐ or remifentanil‐induced respiratory depression. This is related to poor penetration of TRH into the brain compartment but also other causes are discussed. No human data on taltirelin are available. In conclusion, data from animals and human indicate that TRH is not a viable reversal agent of OIRD in awake or anesthetized humans. Further human studies on the efficacy and safety of TRH's more potent and longer lasting analog taltirelin are needed as this agent seems to be a more promising reversal drug. Abstract : Opioid‐induced respiratory depression (OIRD) is a potentially life‐threatening complication of opioid consumption. A possible reversal strategy is treatment of OIRD with the hypothalamic hormone and neuromodulator thyrotropin‐releasing hormone, TRH. In this review, we report that TRH and taltirelin improve OIRD, by causing rapid shallow breathing. In a humans, a continuous infusion of intravenous TRH with doses up to 8 mg, did not reverse OIRD. No human data on taltirelin are available. In conclusion, data from animals and human indicate that TRH is not a viable reversal agent of opioid‐induced respiratory depression in humans.